Modern Pesantren: The Politics of Islamic Education and Problems of Muslim Identity - Andika Novriadi Cibro; Salminawati Salminawati; Usiono Usiono (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The presence of Pesantren has contributed in several ways to the progress that has been made in the field of education in Indonesia. In addition, around 900,000 graduates of Islamic boarding schools have been donated who are ready to continue the spread and da'wah of Islam and participate in building Indonesia's infrastructure which is full of Islamic values in addition to science. This is a significant contribution. Pesantren which is an educational institution that focuses on the formation of Islamic character has a high morality of the Islamic religion in terms of educational politics. This is because the Pesantren adheres to the teachings of the Qur'an and As-Sunnah. Not only that, this situation is because Pesantren is a form of education that emphasizes the cultivation of Islamic character. However, despite the fact that we live in an era of globalization, information, and technology, Pesantren are still the target of criticism for their alleged failure to adapt to globalization in an appropriate way. On the other hand, apart from that, the public education system strengthened by the government also gave birth to new moral problems, which were also the impact of globalization. Collaboration between different educational institutions is now the single most successful strategy to overcome the existing deficiencies in both the Pesantren education system and the general education offered by each school.